Effect of Phosphotungstic Acid toward Composite Membrane for DMFC Application - Suharini, Sri Endang; Permana, Dian; Atmaja, Lukman (IPTEK Journal of Proceedings Series, 2015)
Fuel cell consists of an electrolyte, which connected to the anode and cathode through a polyelectrolyte membrane in which the membrane is capable of delivering protons from the anode toward the cathode. The aim of this study is to know the effect of acid on the membrane composite phosphotungstic chitosan/montmorillonite-silane 10% of the ion exchange capacity, proton conductivity and methanol permeability using a variation of the 0; 0.5; 1.0; 1.5%, respectively. The additions of phosphotungstic acid increased the proton conductivity and ion exchange capacity. However, in this study, the highest proton conductivity on chitosan/ montmorillonite-silane 10%/1.0% phosphotungstic acid caused by a strong hydrophilic nature phosphotungstic acid.